Assessment of Language Education Lecturers’ Computer and Digital Literacy Skills towards E-Learning - Sunday Adejimola Amuseghan; Falakemi Oyeyemi Adeniyi Egbeola; Cyril Abioye Charles Olowoyeye (Universitas Pendidikan Ganesha, 2022)
Computer literacy is just as important in our modern world twenty-first century, digital literacies effectively prepare learners to acquire develop and prepare for better job prospects. The aims of this study analyses assessment of language education lecturers’ computer and digital literacy skills towards e-learning. The study adopted descriptive research of the survey type. The population for the study consisted all lecturers in the department of Language Education Lecturers. Eight language lecturers were purposefully selected for the study. The instrument for data collection was an adapted questionnaire. Descriptive statistics were used to answer the research question with the aid of stastistical product and service solution (SPSS) version 20.0 at 0.05 level of significant. The findings indicated that some of these language education lecturers, though had some knowledge and skills in computers and digital literacy but their depth of applications of computer and digital knowledge and skills was limited or unsophisticated, and therefore did not meet the required computer and digital literacy skill competencies for language teaching and learning in the twenty-first century. This study concluded that computer, digital literacy and communication skills are compulsory requirements for twenty-first century education and job opportunities and Limited knowledge, skills and confidence in certain applications of some tools that are necessary and very relevant for effective use of them in teaching and learning. The study recommends that training in computer-assisted language learning should be included in language teacher education for both pre-service and in-service teachers.